Primary Granulocytic Sarcoma of the Face - Hwang, Jong Ik (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Myeloid sarcoma is a tumor which consists of myeloblasts or immature myeloid cells. This tumor presents in the lymphoid organs, bone, skin, soft tissue, various mucosae and organs, and the central nervous system. Granulocytic sarcoma, an extramedullary acute myeloid leukemia, is also referred to as chloroma (GS) because of its greenish surface color. Granulocytic sarcoma is rare and difficult to diagnose. We can easily misdiagnose this tumor as lymphoma or sarcoma, especially when there is no evidence of hematologic disorders. Immunohistochemical studies are helpful in determining the correct diagnosis. Antibodies to myeloperoxidase, lysozyme, and chloroacetate esterase are used for the diagnosis of granulocytic sarcoma. In addition, detection of cell surface markers such as CD 33, CD 34, CD 68, CD 99, and HLA-DR may be useful. We describe a case of GS that presented with bluish nodules on the right cheek of a 54-year-old woman with immunohistochemical findings for correct diagnosis.